Promoting Engaged Scholarship Among Undergraduate University Students - Jenni Owen; Leslie M. Babinski; David Rabiner (The University of Alabama, 2022)
The School Research Partnership (SRP) is an engaged scholarship program that promotes collaboration among undergraduate students, community partners, and university advisors. In this case study, we describe the Research Consultation Project (RCP), an undergraduate student independent study project that uses a community-based research approach to connect students, faculty, and community partners to help address critical societal issues. In the RCP, undergraduate students function as research consultants for representatives of local school districts or leaders of other community agencies and organizations such as a county commissioner or a nonprofit focused on post-secondary education opportunities for youth. The students work under the supervision of an advisor to address questions posed by the policymaker or practitioner. RCP meets different but complementary needs of the students and partners in ways that bridge student academic and applied learning, research, policy, and practice.